Analisis Nikah Beda Agama dalam Perspektif Maqashid Syari’ah - Ahmad Fauzi; Kemas Muhammad Gemilang; Darmawan Tia Indrajaya (Madania: Jurnal Ilmu-Ilmu Keislaman, 2023)
The marriage performed by the president's Special Staff is a marriage between a non-Muslim man and a Muslim woman. According to the scholars of the four madhhabs, this type of marriage is absolutely prohibited. Even though the majority of Indonesian people are Muslim. So this research was conducted in order to find out the reasons for the prohibition through the maqasid sharia approach. So that the reasons for the prohibition and the law of performing interfaith marriages can be known. This research is categorized as library research with qualitative analysis. The data collection technique is by analyzing references related to interfaith marriage and maqasid sharia. The data obtained through the publish or Perish application were 112 documents, but 12 articles were used. The results of this study are that interfaith marriage is not justified in Islam because it contradicts the five concepts of maqasid sharia; (1) maintenance of religion, namely religion which is a guide to human life, so what is more recommended in religion, it must be better for future life. (2) maintenance of the soul, because in principle they have different teachings and in the end the differences will produce conflicts in it. (3) maintenance of the intellect, namely the intellect that has been contaminated by the doctrines of lust (love), it will not be able to use its intellect properly. It will be easily seduced into misguidance (apostasy) because it does not use its mind and mind properly. (4) maintaining offspring, namely the offspring as the successor of the married couple. But how can the offspring be better who can carry out the mandate as the khalifah of Allah SWT if the marriage has religious differences. (5) maintenance of property, namely someone who marries a different religion then between them can not inherit each other.